Too Many Mind - Michopoulou, Joanna (Murmurations: Journal of Transformative Systemic Practice, 2017)
Stories from everyday life move and provide inspiration to systemic practitioners while at the same time can teach us important lessons about complex relational movements and improvised coordinations. If surprises don’t surprise us and tight rope walking in interactions doesn’t scare us, are we prepared to "live on the edge", in the present moment - a moment when we have to rely on our spontaneous expressive-responsive living bodily activities? In this paper I offer some reflections from my experience from martial arts which has taught me much about the relationship between thinking and doing, about preparing to act and acting in the moment. I discuss how in sparring (a form of mock fighting with a partner, where people make the motions of attack and defence for training purposes) , knowing and acting become one in the moment of interaction with the sparring partner. Spontaneous, unreflective knowing just happens. No inner dichotomies are possible. Due to its demanding and fast nature, sparring provides opportunities to notice how responses get slower and coordination gets ruined when a trained thinking and reflexive mind gets in the way of our embodied awareness in the moments of living interaction. And in our systemic practice, theoretical frameworks and constant "how-to" considerations can alienate us from the people in front of us, from the livingness of our moments together. But what is more beautiful and ethical than two people being intimately open to become directly known to each other, as they emerge through and as part of their interrelating? περίληψη (Greek) Ιστορίες βγαλμένες μέσα από εμπειρίες της καθημερινότητας εμπνέουν τους συστημικούς θεραπευτές και μας δίνουν σπουδαία μαθήματα για τους σύνθετους τρόπους με τους οποίους κινούμαστε μέσα στις σχέσεις μας και για τον αυτοσχεδιασμό ως κομμάτι της διαδικασίας συντονισμού μας με τον άλλο άνθρωπο. Αν οι εκπλήξεις δεν μας εκπλήσσουν και η ισορροπία στο τεντωμένο σχοινί της αλληλεπίδρασης δεν μας τρομάζει, είμαστε άραγε έτοιμοι να σταθούμε στην «κόψη του ξυραφιού», στο τώρα; Το λεπτό εκείνο σημείο όπου θα πρέπει να αφεθούμε στην αυθόρμητη και ζωντανή εκφραστικότητα – απαντητικότητα που πηγαία βγαίνει μέσα από τη σύνδεση μας με τον άλλο άνθρωπο; Σε αυτό το άρθρο προσφέρω κάποιες σκέψεις από την εμπειρία μου με τις πολεμικές τέχνες, η οποία με έχει διδάξει πολλά για τη σχέση μεταξύ σκέψης και πράξης, μεταξύ προετοιμασίας και πραγματικής αλληλεπίδρασης. Συζητάω πώς κατά την προπόνηση της πυγμαχίας, σε ένα είδος ψεύτικης πάλης με κάποια συναθλήτρια, με σκοπό την πρακτική εξάσκηση, η απόσταση μεταξύ της σκέψης και της πράξης μηδενίζεται. Οι κινήσεις έρχονται αυθόρμητα χωρίς σκέψη. Λόγω της απαιτητικής και γρήγορης φύσης του αθλήματος, δίνονται ευκαιρίες για σημαντικές παρατηρήσεις: για παράδειγμα οι αντιδράσεις γίνονται πιο αργές και ο ρυθμός της προπόνησης αποσυντονίζεται μόλις το καλά εκπαιδευμένα σκεπτόμενο μυαλό εμπλακεί και παραγκωνίσει την γνώση που βγαίνει μέσα από την ζωντανή αλληλεπίδραση με την συναθλήτρια την στιγμή της άσκησης.